2010
DOI: 10.1021/jz101250s
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization as a Key Path to Molecular Products in the Gas-Phase Decomposition of Halons

Abstract: NOT THE PUBLISHED VERSION; this is the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in the citation at the bottom of the page. Letters, Vol. 1, No. 20 (2010): pg. 3090-3095. DOI. This article is © American Chemical Society and permission has been granted for this version to appear in e-Publications@Marquette. American Chemical Society does not grant permission for this article to be further copied/distributed or hosted elsewhere without the express permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 49 publications
(106 reference statements)
5
45
0
Order By: Relevance
“…This isomerization pathway could be termed 'roamingmediated', because it involves the migration of the incipient bromine fragment and leads to the iso product species; however, this could not be confirmed without comparison to the same reaction in the gas phase. The isomeric form occupies a shallow minimum on the potential energy surface (PES)-somewhat below the C-Br bond radical dissociation asymptote [12][13][14][15] -and has been proposed 16 to be accessible on the way towards molecular bromine from photoexcited bromoform in the gas phase. This isomerization pathway in the gas phase can only occur through the internal rearrangement of atoms, that is, directly and without the involvement of any other species.…”
mentioning
confidence: 99%
“…This isomerization pathway could be termed 'roamingmediated', because it involves the migration of the incipient bromine fragment and leads to the iso product species; however, this could not be confirmed without comparison to the same reaction in the gas phase. The isomeric form occupies a shallow minimum on the potential energy surface (PES)-somewhat below the C-Br bond radical dissociation asymptote [12][13][14][15] -and has been proposed 16 to be accessible on the way towards molecular bromine from photoexcited bromoform in the gas phase. This isomerization pathway in the gas phase can only occur through the internal rearrangement of atoms, that is, directly and without the involvement of any other species.…”
mentioning
confidence: 99%
“…interest is the potential opening of the channel leading to carbene + dihalogen formation, which remains a topic of interest and controversy in gas-phase experiments up to the present day [33,34]. Molecular beam experiments carried out under single collision conditions show that the dominant process following UV excitation of these polyhalomethanes is cleavage of a carbon-halogen bond, yielding a radical pair [29,30,35,36].…”
Section: Sa Reidmentioning
confidence: 99%
“…For example, in the polyhalomethanes the isomerisation barrier lies much lower in energy than the tight three-centre TS leading to dihalogen elimination [33,41,96]. For example, in the polyhalomethanes the isomerisation barrier lies much lower in energy than the tight three-centre TS leading to dihalogen elimination [33,41,96].…”
Section: Gas-phase Chemistry Of the Iso-halomethanesmentioning
confidence: 99%
“…35,36 This finding is consistent with several other experimental and theoretical studies, 31,37,38 and our recent study of the importance of isomerization as a path to molecular products in halon decomposition has shown that an internal conversion mechanism involving isomerization is insufficient to explain the reported yields of Br 2 in the photolysis of bromoform at 248 nm. 39 The condensed phase photochemistry of bromoform and related halomethanes is slightly less controversial, Figure 1(b). Here, photolysis is known to lead to facile production of the iso-halomethanes following geminate recombination of the initially formed radical pair in the solvent cage, and the isomers have been shown to play a pivotal role in the reactivity of halomethanes in solution.…”
Section: Introductionmentioning
confidence: 99%